Vitamin D levels of anesthesiologists working in tertiary care hospital of South Asian country: An observational study - Sonika Bishnoi; Satinder Gombar; Vanita Ahuja; Neerja Bhardwaj; Jasbinder Kaur (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Vitamin D deficiency is now emerging as a major global health problem. Doctors spend most of their time indoors and hence, have very low sun exposure. With limited studies on vitamin D levels of anesthesiologists and no published study from South Asian countries, we planned to determine vitamin D levels in anesthesiologists. Material and Methods: One hundred twenty anesthesiologists, working in two tertiary care hospitals, were enrolled in this study. The participants were asked to complete the questionnaire and blood samples were drawn at the same sitting for measuring serum 25(OH) D and serum calcium levels. A subgroup analysis of anesthesiologists was done based on vitamin D status levels defined as per Endocrine society clinical practice guidelines 2011 on vitamin D deficiency. Vitamin D deficiency: 25(OH) D <20 ng/ml (<50 nmol/l), Vitamin D insufficiency: 25(OH) D of 21-29 ng/ml (52.5-72.5 nmol/l), Vitamin D sufficiency: 25(OH) D of ≥30 ng/ml (≥75 nmol/l). Results: The mean working hours in a day [mean ± standard deviation (SD)] were 10.70 ± 1.56 hours with a range of 8-15 hours. The mean ± SD level of vitamin D in anesthesiologists was 14.56 ± 9.39 ng/ml with a range of 5.30-58.00 ng/ml. Out of 120 anesthesiologists, 101 (84.2%) anesthesiologists had deficient levels of vitamin D, 10 (8.3%) had insufficient levels, and 9 (7.5%) anesthesiologists had sufficient levels of vitamin D. Majority of the anesthesiologists had normal serum calcium levels. A total of 91.5% of doctors had vitamin D deficiency who were not taking vitamin D supplement groups as compared to 28.6% in doctors who had taken vitamin D supplements in the past. Conclusion: Prevalence of vitamin D deficiency/insufficiency was high among anesthesiologists. However, levels were optimal in professionals taking vitamin D supplements.